Analysis of emergency situations on the process of thermal power plants using mathematical apparatus of Petri nets (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Article is dedicated to the issues of accident scenarios analysis on the process of thermal power plants. The theoretical foundations of the graphical and analytical representation of Petri nets are shown. The article describes the steam cycle process and listing of its technology protections. A state model for power unit equipment and technological protections under the influence of changes in critical process parameters (steam’s temperature, pressure, level) is presented. Conclusions about the plans for further work in this direction are proposed.